Sinobatis brevicauda n. sp., a new deep-water legskate (Rajiformes, Anacanthobatidae) and first generic record from the western Indian Ocean - Weigmann, Simon; Stehmann, Matthias F.w. (Zootaxa, 2016)
A new deep-water legskate, Sinobatis brevicauda, is described based on two specimens caught on the remote Saya de Malha Bank in the central western Indian Ocean. The new species is easily distinguished from all other described anacanthobatids by the short tail. It is the only Sinobatis species described from the western Indian Ocean and differs from the other anacanthobatid legskates in this area by its large size and light coloration. All other species of Sinobatis are described from the eastern Indian and, particularly, western Pacific oceans. In addition to the short tail, the new species clearly differs from its morphologically closest congener, the Australian S. bulbicauda, in a bicolored white and grayish ventral coloration with gray and white blotches (vs. uniformly pale or white and skin somewhat translucent) and a filamentous tail without flattened, bulbous tip. Furthermore, it is distinguished by several morphometric and meristic differences, e.g. a longer body (length 65% TL vs. 39–61% TL), longer head (dorsal length 34% TL vs. 21–31% TL, ventral length 41% TL vs. 23–36% TL), longer snout (preorbital length 28–29% TL vs. 14–26% TL, preoral length 30% TL vs. 16–28% TL, prenasal length 28% TL vs. 14–25% TL), and fewer diplospondylous (102–112 vs. 121–142) and total (131–141 vs. 148–168) vertebrae. S. brevicauda clearly differs from the other anacanthobatids in the western Indian Ocean, Anacanthobatis marmorata and Indobatis ori, by having a much shorter tail, strongly different coloration, much larger size, and in many morphometric and meristic differences.